Spin and torsion in gravitation - Sabbata, Venzo De (World Scientific, 1994)
This book gives an exposition of both the old and new results of spin and torsion effects on gravitational interactions with implications for particle physics, cosmology etc. Physical aspects are stressed and measurable effects in relation to other areas of physics are discussed. Among the topics discussed are: alternative ways of unifying gravity with electroweak and strong interactions by an energy dependent spin torsion coupling constant; the idea that all interactions can be understood as originating from spin curvature coupling; the possibility of cosmological models with torsion providing a solution to the cosmological constant problem; and a demonstration that torsion can lead directly to the quantization of space-time itself.